Determinant Analysis of the Quality of Company Financial Reports in East Kalimantan, Indonesia - Mat Juri; La Ode Hasiara; Noor Fachman Tjetje; Muhammad Suyudi (International Journal of Artificial Intelligence Research, 2022)
The objectives of this study were to establish Management Commitment (MC), human capital, knowledge, honesty, and communication, either directly or indirectly. This study used a quantitative approach with a Structural Equation Modeling (SEM) model. The results of this study showed that: 1) Mana¬gement Commitment, accounting standards, and human capital has a positive and significant im¬pact on the quality of financial reports, 2) Accounting knowledge, Management Commitment, and human capital have a significant positive impact on the quality of communication, 3) Accounting know¬¬ledge and communication does not affect the quality of financial reports, 4) Human capital does not affect the quality of communication. It was concluded that Management Commitment, human capital, and accounting knowledge dominate the quality of the financial reports